Characterization of citrus apirenic fresh fruit cultivars by morphological descriptors - Radmann, Elizete Beatriz; Oliveira, Roberto Pedroso de (Pesquisa Agropecuaria Brasileira, 2003)
The aim of this work was to characterize nine citrus fresh fruit cultivars by morphological descriptors. Four year-old plants of sweet oranges 'Lane Late', 'Navelate', 'Navelina' and 'Salustiana'; mandarins 'Clemenules', 'Marisol' and satsuma 'Okitsu'; and hybrids 'Nova' and 'Ortanique', grafted in Trifoliata and cultivated in pots of 100 L, were analyzed. Twenty eight morphological descriptors were selected, making possible a rapid and efficient characterization of the cultivars, including the sweet oranges. The standards obtained are in conformity with the phylogenetic relations among the species studied. The standards can be used in certification, breeding, and germplasm conservation programs.
Keywords: hybrids; morphological markers; sweet oranges; mandarins